2017
DOI: 10.1111/1346-8138.13729
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster with meningitis in a vaccinated, immunocompetent child

Abstract: Herpes zoster with meningitis in a vaccinated, immunocompetent childDear Editor, Meningitis is a rare complication of herpes zoster (HZ) and its incidence was reported as only 0.5%. 1 Central nervous system complication most often occurs in immunocompromised patients or the elderly by infection with wild-type varicella zoster virus (VZV), although several cases have occasionally been reported with vaccine-strain VZV. 2,3 A healthy 7-year-old boy presented with a 3-day history of left facial, painful, pruritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In all these cases any involvement of cerebral parenchyma was demonstrated and this supports one of unique feature of our case. To our knowledge, some cases of CNS infection due to reactivation of VZV in vaccinated children have been reported, but genotyping verification of the vaccine strain was available in a relatively small number of patients [16][17][18]. Regardless our patient, as the other two showed in the table, presented varicella during their infancy and they did not get vaccination.…”
Section: Discussionmentioning
confidence: 67%
“…In all these cases any involvement of cerebral parenchyma was demonstrated and this supports one of unique feature of our case. To our knowledge, some cases of CNS infection due to reactivation of VZV in vaccinated children have been reported, but genotyping verification of the vaccine strain was available in a relatively small number of patients [16][17][18]. Regardless our patient, as the other two showed in the table, presented varicella during their infancy and they did not get vaccination.…”
Section: Discussionmentioning
confidence: 67%
“…Past medical history was unre- or without rash. Zosteriform rashes had developed before any symptoms of meningitis in some patients, easily leading to the suspicion of VZV meningitis [5][6][7] . According to a recent retrospective study of 24 patients with meningitis and meningoencephalitis who showed typical zosteriform skin rashes, CSF tests and intra- Fig.…”
Section: Case Reportmentioning
confidence: 99%